Primary squamous cell carcinoma of breast with ipsilateral axillary lymph node metastasis: An unusual case - Mitra, Bhaskar (2011)
INTRODUCTION: Pure squamous cell carcinoma of the breast [SCCB] is rare. PRESENTATION OF CASE: We report a case of primary squamous cell carcinoma of breast with ipsilateral axillary lymph node metastasis in a 58year old woman. DISCUSSION: It is a breast carcinoma entirely composed of metaplastic squamous cells that may be keratinized, non-keratinized or spindled. The pure squamous cell carcinoma usually present with central cystic cavity, which we found in our case, also supported by immunohistochemical evidence. CONCLUSION: Although a rare breast cancer subtype, SCCB is of considerable interest due to its pathological heterogeneity and differences in clinical behavior and less reported occurrence of nodal metastasis.